Shell Colour Diversity in Marine Molluscs: From Current Knowledge to Future Aquaculture Applications - Biyang Hu; Hong Yu; Chengxun Xu; Lingfeng Kong; Shikai Liu; Qi Li (Reviews in Aquaculture, 2025)
Mollusc shell colour represents an important economic trait contributing to product marketability in aquaculture. Marine molluscs with diverse shell colours and patterns are valuable models for animal colouration mechanisms study. Recent progress in marine mollusc shell colour research has been propelled by investigations of shell‐colour variants, advancements in high‐throughput sequencing technologies, and research into metabolic regulatory mechanisms for pigment biosynthesis. This review synthesizes current advancements in genetic architecture, gene regulatory networks and pigment metabolic processes governing shell colour variation in marine molluscs. In this review, insights gained from genetic studies uncover diverse inheritance patterns, key loci and present shell‐colour‐related transcriptomic datasets along with integrative multi‐omics studies. Moreover, distribution, metabolic networks and functional gene linkages of major pigments (melanin, carotenoids, and porphyrins) are characterized, while ommochromes are also discussed. Furthermore, environmental, dietary and structural factors influencing shell colour are listed. By synthesizing current findings, this review offers a detailed overview of the common factors influencing shell colour across marine mollusc species and probes the potential implications of shell colour studies for aquaculture. Future research directions emphasize pigment characterization, pigment transport mechanism studies and integrative multi‐omics approaches to bridge genetic and chemical understandings. In summary, this review outlines the current progress on marine mollusc shell colouration, provides referable research directions on shell‐colour‐related molluscs, and enhances understanding of animal colouration mechanisms.